Pengaruh Peran Guru Terhadap Motivasi Belajar Peserta Didik dalam Pembelajaran Sosiologi Kelas XI IPS di SMAN 1 Padang Gelugur Pasaman - Nurharli, Ariyanti; Junaidi, Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
This research was motivated by the low learning motivation of students in learning sociology for class XI IPS at SMAN 1 Padang Gelugur, Pasaman, the low motivation to learn students was seen from the movements of students during the learning process, and student learning outcomes in learning sociology. This is interesting to study because in the process of learning activities there is a need for motivation, where the motivation of students greatly determines how these students act in the learning process but there are still students who have low motivation so that this becomes a problem that needs to be studied more deeply. This study aims to analyze the relationship between the teacher's role and students' motivation in learning sociology in class XI IPS at SMAN 1 Padang Gelugur, Pasaman. This type of research is correlational, quantitative approach with ex post facto method. The number of samples is 68 students. The sampling technique used is proportional random sampling technique. This study uses the role theory of Robert Linton and Biddle and Thomas, then the researcher also uses the behavioristic learning theory proposed by Gagne and Berliner. Data collection is done by distributing questionnaires (questionnaire) directly. Then test requirements analysis using 3 classical assumption tests, namely normality test, linearity test and heteroscedasticity test. The data collected were analyzed using product moment correlation analysis techniques and simple linear regression analysis, while for hypothesis testing using t statistical tests and calculating the coefficient of determination (R2). The results of this study indicate that there is a positive and significant relationship between the teacher's role and students' learning motivation in learning sociology for class XI IPS at SMAN 1 Padang Gelugur, Pasaman with a large correlation (R) of the teacher's role with students' learning motivation of 0.532 or 53% and the coefficient of determination R square (R2) is 0.283 or 28% and the remaining 72% is influenced by other variables or factors that are not the focus of this study.